Physiological and psychological effects of a 12-week home-based telemonitored training in metabolic syndrome - Máthéné Köteles, Éva; Rafael, Beatrix; Korom, Andrea; Vágvölgyi, Anna; Ábrahám, Judit Erzsébet; Domján, Andrea; Szűcs, Mónika; Nemes, Attila; Barnai, Mária; Lengyel, Csaba; Kósa, István (Frontiers in Cardiovascular Medicine, 2023)
Background: Metabolic Syndrome (MetS) increases the risk of cardiovascular diseases and affects around one fourth of the population worldwide. In the prevention and treatment regular exercise trainings are inevitable. Providing personal supervision in out/inpatient care settings for such a large target population challenges the healthcare systems, but using telemonitoring of the home-performed trainings could be a promising and widely available option. Objectives: The aim of this study was to evaluate the physiological and psychological effects of a 12 week home-based physical training programme, telemonitored by widely available fitness devices on parameters of MetS patients. Methods: 55 MetS patients (mean age 49.19±7.93 years) were involved in the study. They were asked to perform 3-5 sessions of exercise activity (min. 150 minutes) each week for 12 weeks. Trainings were monitored off-line by heart rate sensors, a fitness application and a cloud-based data transfer system. Physiotherapists supervised, coached and fedback the trainings through an online coach system. We investigated different anthropometric parameters, maximum exercise and functional capacity levels, laboratory parameters, the level of depression, insomnia, vital exhaustion and well-being as well. Results: Patients showed statistically significant changes in: all the measured waist and hip circumferences; six-minute walk distance (6MWD; from 539.69±78.62m to 569.72±79.96m, p<0.001); maximal exercise capacity (11.02±2.6 MET to 12.14±2 MET, p<0.001), stress-electrocardiogram duration time (13.74±3.29 min to 15.66±2.64 min, p<0.001); body weight (98.72±21.7 kg to 97.45±21.76 kg, p=0.004); high-density lipoprotein cholesterol (n=45, 1.28±0.31 mmol/L to 1.68±0.36 mmol/L, p<0.001); fasting plasma glucose (FPG; n=47, 6.16±1.26 mmol/L to 5.44±1.31 mmol/L, p=0.001); glycated hemoglobin A1c (HbA1c; n=41, 6.22±0.68 % to 5.87±0.78 %, p=0.01). We found statistically significant decrease of the overall scores of the Maastricht Vital Exhaustion Questionnaire, from 3.37±2.97 points to 2.63±2.70 points (p<0.05) and a significant increase of the overall scores of the WHO Well-Being Scale from 9.92±2.59 points to 10.61±2.76 points (p<0.05). Conclusion: A 12-week home-based telemonitored training supported by an affordable, commonly available device system produces positive, statistically significant changes in many core components in MetS patients. Telemonitoring is a cheap method for coaching and feeding back the home-based interventions.